PEMAHAMAN MAHASISWA BK TERHDAP FENOMENA CHILD FREE (PERNYATAAN INFLUENCER GITA SAVITRI DI YOUTUBE) STUDI PADA MAHASISWA BK UNTIRTA - Meilla Dwi Nurmala; Bangun Yoga Wibowo (Jurnal Penelitian Bimbingan dan Konseling, 2024)
Starting from a statement issued by influencer Gita Savitri. The term Childfree began to be recognized by the Indonesian people. This childfree phenomenon affects the thinking of productive-age students not to have children. In line with easily accessible information and the lack of religious knowledge and household psychology. Childfree is defined by a desire or better known as not having children in his life. Oxford Dictionary describes childfree as a condition or situation without children voluntarily. This research uses a descriptive method, which is to look at existing phenomena and what is happening, namely not giving treatment to the research subject. The results found that when looking at this childfree phenomenon there were 60.7% of respondents who chose to agree with this childfree phenomenon. And the remaining 39.3% chose not to agree with this childfree phenomenon. There are differences in understanding among BK Untirta students towards this phenomenon. Each group has reasons for the impact that will occur due to this childfree phenomenon, both positive and negative impacts.Keywords: Childfree, Counseling Students, Pros and Cons